Update of HIV infection in pregnancy - HO, King Man; TSE, Hei Yee (Hong Kong Journal of Gynaecology, Obstetrics and Midwifery, 2023)
In the past two decades, human immunodeficiency virus (HIV) infection has developed from isolated reports of clusters of immunodeficency illness in homosexual men to a global pandemic affecting men and women alike, even babies. Significant progress was made in combating the disease including elucidation of the causative agent and modes of transmission, developments of antiretroviral agents and the now renowned "cocktail therapy" rendering the disease control to chronic illness instead of lethal disease, and perhaps in the forseeable future,development of an effective vaccine. Globally, more than 70% of HIV infections are a result ofheterosexual transmission and over 90% of infections in children result from mother-to-child infection (MTCT). With effective interventions to reduce MTCT, obstetricians and midwives can contribute to the control of the pandemic.